Suggested actions for CGIAR leaders - CGIAR Institutional Learning and Change Initiative; CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation; International Livestock Research Institute (2008)
This Brief provides practical, concrete action options for CGIAR management to address the key issues raised at the Rethinking Impact Workshop (RIW): Understanding the complexity of poverty and change.